Survival Outcomes Associated With Clinical and Pathological Response Following Neoadjuvant FOLFIRINOX or Gemcitabine/Nab-Paclitaxel Chemotherapy in Resected Pancreatic Cancer. Issue 3 (September 2019) - Macedo, Francis I.; Ryon, Emily; Maithel, Shishir K.; Lee, Rachel M.; Kooby, David A.; Fields, Ryan C.; Hawkins, William G.; Williams, Greg; Maduekwe, Ugwuji; Kim, Hong J.; Ahmad, Syed A.; Patel, Sameer H.; et al.
Abstract : Objective: To compare the survival outcomes associated with clinical and pathological response in pancreatic ductal adenocarcinoma (PDAC) patients receiving neoadjuvant chemotherapy (NAC) with FOLFIRINOX (FLX) or gemcitabine/nab-paclitaxel (GNP) followed by curative-intent pancreatectomy. Background: Newer multiagent NAC regimens have resulted in improved clinical and pathological responses in PDAC; however, the effects of these responses on survival outcomes remain unknown. Methods: Clinicopathological and survival data of PDAC patients treated at 7 academic medical centers were analyzed. Primary outcomes were overall survival (OS), local recurrence-free survival (L-RFS), and metastasis-free survival (MFS) associated with biochemical (CA 19–9 decrease ≥50% vs <50%) and pathological response (complete, pCR; partial, pPR or limited, pLR) following NAC. Results: Of 274 included patients, 46.4% were borderline resectable, 25.5% locally advanced, and 83.2% had pancreatic head/neck tumors. Vein resection was performed in 34.7% and 30-day mortality was 2.2%. R0 and pCR rates were 82.5% and 6%, respectively. Median, 3-year, and 5-year OS were 32 months, 46.3%, and 30.3%, respectively. OS, L-RFS, and MFS were superior in patients with marked biochemical response (CA 19–9 decrease ≥50% vs <50%; OS: 42.3 vs 24.3 months, P < 0.001; L-RFS-27.3 vs 14.1 months, P = 0.042; MFS-29.3 vs 13 months, P = 0.047) and pathological response [pCR vs pPR vs pLR: OS- not reached (NR) vs 40.3 vs 26.1 months, P < 0.001; L-RFS-NR vs 24.5 vs 21.4 months, P = 0.044; MFS-NR vs 23.7 vs 20.2 months, P = 0.017]. There was no difference in L-RFS, MFS, or OS between patients who received FLX or GNP. Conclusion: This large, multicenter study shows that improved biochemical, pathological, and clinical responses associated with NAC FLX or GNP result in improved OS, L-RFS, and MFS in PDAC. NAC with FLX or GNP has similar survival outcomes. Abstract : Supplemental Digital Content is available in the text